Existential and Psychological Problems of Aging: The Perspective of Ukrainian Lyrics’ Art Representation - Shaf, O. V.; Oliynyk, N. P. (Anthropological Measurements of Philosophical Research, 2021)
Purpose. Aging is intricate process of self-transformation in view of involution of body, loss of sexual attractiveness, but at the same time, old age is a time for reconsideration of self-existence in time and in the world within coherence of life sense targets and their (successful) realization. Unique individual experience of growing old implemented in Ukrainian literature (and lyrics) can complete the data received by gerontology. Moreover gender approach in literary gerontology highlights masculine / feminine phenotypical features of internal reverberating of aging. Theoretical basis. To inquire into existential and psychological problems of aging exemplified in the twentieth-century Ukrainian Lyrics it is seems to be the most effective to employ philosophical (A. Anhelova, V. Demidov, T. Dziuba, K. Pigrov, S. Lishaev, O. Khrystenko and others) and psychological (O. Berezina, S. Hamilton, V. Savchyn, Y. Sapogova and others) approaches in gerontology, as well as feministic studies on elder female body discrimination, in particular in literature (K. Woodward, J. King). Originality. This research paves the way to the development of gender and literary dimensions in Ukrainian gerontology and anthropology in general. Some of the existential and psychological problems of aging (as anxiety of body involution and decline of strength, as well as finding the compensatory pleasure in wisdom and spiritual treasures) are revealed on the material of 20th-century Ukrainian poetry (N. Livytska-Kholodna, B. Lepkyi, M. Zerov, Yurii Klen, Y. Malaniuk, Y. Tarnawsky, I. Zhylenko, S. Yovenko and others). The individual lyric experience of aging in different gender moods is anchored mostly in psychic, mental, sense-life strategies. Conclusions. Among the feminine strategies of aging self-reception there are observation of own elder body with anxiety and fear, its "invisibility", deepened feelings of loneliness, self-estrangement, but also finding the sense of life and soul harmony in own family, offspring. Masculine self-reception of aging deals with ideal spiritual model of Wise old man – more abstract than personal; masculine anxiety is caused by physical bodily declining, not attractiveness, but strength and power loosing.